bunyod THE IMPORTANCE OF TEACHING FOREIGN LANGUAGES AT TECHNICAL HIGHER EDUCATION SYSTEM: THE IMPORTANCE OF TEACHING FOREIGN LANGUAGES AT TECHNICAL HIGHER EDUCATION SYSTEM - Bazarov, Bunyod (Журнал иностранных языков и лингвистики, 2022)
One of the actual problem of nowadays is language skills. The number of professional information in foreign languages are great and developing. The most dynamic in terms of international integration and in exchanging data are the branches of economy, law, industry, provision and supply of market economy and others, their rapid development requires specialists to know foreign languages according to branches.